2010
DOI: 10.4314/njps.v22i1-2.54895
|View full text |Cite
|
Sign up to set email alerts
|

Ocular effects of chronic exposure to welding light on calabar welders

Abstract: Summary:It was generally observed that welders in Calabar, Nigeria did not always wear their protective goggles during welding. Since chronic exposure to welding light can impair vision this study was done to assess the effect of exposure to welding light on ocular function of welders in Calabar, Nigeria. There were 195 subjects comprising 110 welders (test) and 85 control subjects. Both groups were all male and had similar age range. The tests employed were clinical examination for ocular disorders, assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
16
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 5 publications
11
16
3
1
Order By: Relevance
“…In a study in Mauritius, 85.5% of the women had never heard about HRT and of the 14.5% who said that they heard about it, over 30% said that they had no idea what it was. [16] None of the women studied was on HRT and this finding was similar to the finding in Ibadan where none of the participants was on HRT. [8] Okonofua et al reported that six out of the 563 (1.1%) menopausal women studied at Ile-Ife were on HRT.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In a study in Mauritius, 85.5% of the women had never heard about HRT and of the 14.5% who said that they heard about it, over 30% said that they had no idea what it was. [16] None of the women studied was on HRT and this finding was similar to the finding in Ibadan where none of the participants was on HRT. [8] Okonofua et al reported that six out of the 563 (1.1%) menopausal women studied at Ile-Ife were on HRT.…”
Section: Discussionsupporting
confidence: 88%
“…[12] It was generally observed that welders in Calabar, Nigeria, did not always wear their protective goggles during welding; human behavior is complicated and is often affected by sociocultural factors apart from awareness. [16] A statistically significant lower level of utilization of protective eye devices among the gas welders compared with the arc welders was noted in this study. This may be related to the lower level of awareness about protective eye devices among the former.…”
Section: Discussionmentioning
confidence: 59%
“…The results of this study are consistent with previous research by Sabitu et al 5 that concluded that some of the effects of welding on health include photokeratitis or arc eye. This results was in accordance with the opinion of Davies 8 which concluded that welding emits a wide spectrum of radiations ranging between 200-1,400 nm. These radiations include ultraviolet (UV) rays (200-400 nm).…”
Section: Discussionsupporting
confidence: 81%
“…Common health effects in the eyes, lungs, skin and fertility are reported among the welders [1, 2]. The employment of safety measures to minimize the hazards and the use of personal protective equipment has been seen to decrease morbidity and mortality among the welders.…”
Section: Introductionmentioning
confidence: 99%